2007
DOI: 10.1590/s0004-27302007000600010
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein in subjects with type 2 diabetes mellitus and/or high blood pressure

Abstract: Type 2 diabetes mellitus (DM2) and high blood pressure (HBP) may contribute to the development of cardiovascular disease, and inflammation may be an important factor in these diseases. In the present study, plasma levels of high-sensitivity C-reactive protein (hs-CRP) were measured in subjects with DM2 and/or HBP and compared to those of normal subjects. Eighty-nine subjects were analyzed for hs-CRP, including 13 normotensive patients with DM2, 17 patients with HBP, 34 hypertensive patients with DM2 (DM2+HBP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
6
15
0
7
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] So there was assumption that hypertensive individuals should have higher CRP. Like other studies 10,[14][15][16] we also got the same findings: Hypertensive subjects have higher CRP than those of normotensive subjects. There are many studies carried out to find the correlation whether higher level of CRP may lead to hypertensive complications, but it still remains controversial.…”
Section: Discussionsupporting
confidence: 88%
“…[3][4][5][6][7][8][9][10][11] So there was assumption that hypertensive individuals should have higher CRP. Like other studies 10,[14][15][16] we also got the same findings: Hypertensive subjects have higher CRP than those of normotensive subjects. There are many studies carried out to find the correlation whether higher level of CRP may lead to hypertensive complications, but it still remains controversial.…”
Section: Discussionsupporting
confidence: 88%
“…The difference might be due to the different inflammatory conditions involved, since acute myocardial infarction causes acute inflammation and oxidative stress, whereas type 2 diabetes is a chronic inflammatory disorder [2, 30]. Although the serum levels of CRP, commonly used as a marker of inflammation, were not significantly increased in the T2D groups, it should be noted that an increase in CRP is not a universal feature of T2D [32, 33]. This suggests that inflammation may not be the major factor leading to the T2D observed, at least in this particular set of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al [41] suggested that variations in circulating hsCRP, even within the normal range is involved in the interrelation of cardiovascular risk factors, like age, smoking, obesity, high blood pressure and dyslipidemia, which are supposed to promote atherosclerosis and ultimately provoke cardiovascular diseases, such as coronary artery disease. Lima et al [42] observed that patients who suffered from both hypertension and diabetes had higher levels of hsCRP than normal subjects; indicating that patients with two associated diseases have a more active inflammatory state.…”
Section: Discussionmentioning
confidence: 99%